Efektivitas Aplikasi Eduktif Quizziz dalam Mengoptimalkan Kemampuan Mengenal Mata Uang Peserta Didik Tunagrahita di SLB Harapan Mulia Kota Jambi - Salsha Julia; Keisya Damia Garbita; Syah Akbar; Beny Rahim; Muhammad Ilham; Jelpa Periantalo (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The research aims to explore how Quizziz can be effective in improving the understanding of currency recognition in learners with disabilities. The research used a quantitative approach and an experimental method of one group pre-test post-test design to collect data on student learning outcomes. Data collection was done through written tests in the form of multiple choice, with analysis using parametric statistical techniques and Paired Sample T-Test test. The data findings showed that the average student pretest score was 66.0 and which then increased to 89.3 on the posttest, with an average difference of 23.3 points. The statistical test resulted in a significance value of p = 0.004, which is a value that shows the significance of the difference and increase in scores. The increase in the results obtained is an indication that when learning is carried out with gamification and visual-based media such as Quizizz is able to provide assistance in helping students understand the basic concepts of currency and increase learning motivation through an attractive and interactive display. Thus, it can be concluded that the Quizizz application can be a feasible alternative for use in learning, especially to increase the independence of students with disabilities in daily life through mastery of currency recognition material.